2019
DOI: 10.3390/jcm8081120
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Trends in Dry Eye Disease and Factors Associated with Ophthalmic Follow-up Discontinuation in Japan

Abstract: Despite the importance of dry eye disease (DED) treatment, the rate of DED treatment discontinuation, especially discontinuation of ophthalmic follow-up, remains unknown. This study aimed to assess the prevalence and risk factors of ophthalmic follow-up discontinuation for DED. A cross-sectional survey of 1030 participants was conducted using a self-administered web-survey instrument. We collected lifestyle information, history of DED diagnosis, types of treatment, frequency of eye-drop usage, symptoms, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This issue appears to be even more important considering that tear substitutes are an over-the-counter preparation and a plethora of different types are available on the market. A recent study showed that more than two-thirds of the patients with persistent DED reported having discontinued their treatment, and that only one tenth of them was using the same type of tear substitute prescribed by the physician during the visit [43].…”
Section: False Myth #7: "Dry Eye Disease Does Not Influence Surgical Outcomes"mentioning
confidence: 99%
See 1 more Smart Citation
“…This issue appears to be even more important considering that tear substitutes are an over-the-counter preparation and a plethora of different types are available on the market. A recent study showed that more than two-thirds of the patients with persistent DED reported having discontinued their treatment, and that only one tenth of them was using the same type of tear substitute prescribed by the physician during the visit [43].…”
Section: False Myth #7: "Dry Eye Disease Does Not Influence Surgical Outcomes"mentioning
confidence: 99%
“…Medical Fact #9: "Tear Substitutes Should Be Prescribed and Used with Regular Dosing" a plethora of different types are available on the market. A recent study showed that more than twothirds of the patients with persistent DED reported having discontinued their treatment, and that only one tenth of them was using the same type of tear substitute prescribed by the physician during the visit [43]. An old conception of DED therapy was that the addition of a tear volume to the dry ocular surface alone should be able to solve the disease.…”
Section: False Myth #7: "Dry Eye Disease Does Not Influence Surgical Outcomes"mentioning
confidence: 99%
“…Although DED is not curable, timely and efficient treatment can relieve the symptoms. However, one study found that patients tended to discontinue follow-ups as DED prolonged after diagnosis ( 35 ). Thus, timely and comprehensive education on patient is essential to prevent their discouragement on following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…EDE or ADDE with consideration of the presence of symptoms and clinical signs [331,339]. A recent concept in CLIDE management suggested by the Japanese Dry Eye Society in their report on Tear Film Oriented Therapy [347,348] focused on targeting either the tear film or the contact lens or both [296].…”
Section: Managementmentioning
confidence: 99%